Skin lesions of Birt-Hogg-Dubé syndrome: Clinical and histopathological findings in 31 Japanese patients who presented with pneumothorax and/or multiple lung cysts. Issue 1 (January 2018) - Iwabuchi, Chikako; Ebana, Hiroki; Ishiko, Akira; Negishi, Azusa; Mizobuchi, Teruaki; Kumasaka, Toshio; Kurihara, Masatoshi; Seyama, Kuniaki
Highlights: The prevalence of skin lesions was reported to be low (approximately <30%) in Japanese BHDS patients. However, it was as high as 74% of BHDS patients who exhibited pulmonary manifestation that prompted the skin biopsy for diagnosis. The detection rate of fibrofolliculomas/trichodiscomas increased significantly in older patients and dermoscopy was a useful adjunct. Location of FLCN mutation had no correlation with the presence of skin lesions or frequency of fibrofolliculoma/trichodiscoma. Abstract: Background: Birt-Hogg-Dubé syndrome (BHDS) (OMIM #135150) is an autosomal dominant disease, characterized by fibrofolliculomas (FFs) of the skin, pulmonary cysts with/without pneumothorax, and renal tumors. The prevalence of skin manifestations reported for Japanese BHDS patients is lower (<30%) compared with that of Western countries (75 ∼ 90%), which appear to be underestimated. Objective: To precisely examine the prevalence of skin lesions with dermoscopy and histopathology with reference to genetic analyses. Methods: We studied 31 patients (47.0 ± 13.2 years old, range 15–71) consisting of 26 unrelated families consecutively from May 2013 to June 2015 specifically for skin-colored papules on their faces and cervicothoracic regions. Patients initially suspected of BHDS from multiple pulmonary cysts that resulted in pneumothorax (30/31; 96.8%) received dermoscopic examinations and skin biopsies if applicable. The diagnosis of BHDS was established by folliculin ( FLCN ) genetic testing, and the results were compared to the histopathological findings of FFs or trichodiscomas (TDs). Results: FLCN germline mutation was demonstrated in 25/26 (96.2%) unrelated families tested and 28/29 patients (96.6%) tested. Skin lesions were recognized in 26/31 patients (83.9%); skin biopsies were performed in 23 patients of whom FFs and/or TDs were histologically demonstrated in 17 (73.9%). Although our study population included patients whose skin manifestations were evaluated prior to or after FLCN genetic testing, skin lesions were clearly prevalent and recognizable irrespective of whether genetic testing was or wasn't done. When examined with dermoscopy, distinct FFs appeared as well-demarcated areas of pallor with central follicular openings in 13 of 15 FF-bearing patients (86.7%); however, those manifestations were not recognized for TD. Conclusions: Skin lesions appear to be more prevalent than previously reported (<30% vs.73.9%) in Japanese BHDS patients. Dermoscopy is a useful diagnostic aid for finding FFs.